Simvastatin Posttreatment Controls Inflammation and Improves Bacterial Clearance in Experimental Sepsis - Flora Magno de Jesus Oliveira; Cassiano Felippe Gonçalves-de-Albuquerque; Isabel Matos Medeiros de Moraes; Patrícia Alves Reis; Vinicius Novaes Rocha; Patrícia Torres Bozza; Adriana Ribeiro Silva; Hugo Caire de Castro Faria Neto (Mediators of Inflammation)
Sepsis is characterized by a life-threatening organ dysfunction caused by an unbalanced host response to microbe infection that can lead to death. Besides being currently the leading cause of death in intensive care units worldwide, sepsis can also induce long-term consequences among survivors, such as cognitive impairment. Statins (lipid-lowering drugs widely used to treat dyslipidemia) have been shown to possess pleiotropic anti-inflammatory and antimicrobial effects. These drugs act inhibiting 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, an enzyme that catalyzes the conversion of HMG-CoA to mevalonate, the limiting step in cholesterol biosynthesis. In this work, we evaluated the therapeutic effects of simvastatin in an animal model of sepsis. In previous study from our group, statin pretreatment avoided cognitive damage and neuroinflammation in sepsis survivors. Herein, we focused on acute inflammation where sepsis was induced by cecal ligation and puncture (CLP), and the animals were treated with simvastatin (2 mg/kg) 6 h after surgery. We measured plasma biochemical markers of organ dysfunction, cell migration, cell activation, bacterial elimination, production of nitric oxide 24 h after CLP, survival rate for 7 days, and cognitive impairment 15 days after CLP. One single administration of simvastatin 6 h after CLP was able to prevent both liver and kidney dysfunction. In addition, this drug decreased cell accumulation in the peritoneum as well as the levels of TNF-α, MIF, IL-6, and IL-1β. Simvastatin diminished the number of bacterial colony forming units (CFU) and increased the production of nitric oxide production in the peritoneum. Simvastatin treatment increased survival for the first 24 h, but it did not alter survival rate at the end of 7 days. Our results showed that posttreatment with simvastatin hampered organ dysfunction, increased local production of nitric oxide, improved bacterial clearance, and modulated inflammation in a relevant model of sepsis.